Waste Footprint And Accounting Methods - Vološinová Dagmar; Ansorge Libor; Stejskalová Lada; Chernysh Yelizaveta (E3S Web of Conferences, 2023)
A comprehensive accounting of waste generation is the basis for the development of an effective waste management policy and makes it possible to identify the sources of waste generation. Identifying the major waste-producing sectors allows the waste policy to be targeted and measures to be taken with high efficiency. The aim of this study is to expand the environmental footprint of waste under an interdisciplinary perspective and propose a methodological approach to account for waste production pathways. The study used an interdisciplinary approach based on the integration of different methods for estimating waste accumulation and its qualitative characteristics using bibliometrics and different databases. Waste production can be viewed from the perspectives of both producers and consumers (perspectives based on production and consumption). Differences in the interpretation of the term "waste footprint" on the principles of circular economy were identified. At the same time, it is close to the water footprint principles, where the amount of fresh water used is included in the water footprint indicator, but only the amount that is consumed and cannot be reused. Similarly, the principle can be established that the waste footprint indicator should include only the amount of waste that is released into the environment and is no longer used as input in another production chain. Thus, the total waste production in a country is not in itself a valid measure of the burden on the environment. A formalization of the waste footprint approach is proposed, taking into account the possibility of waste recycling, using food waste as an example.